Global Visualization and Knowledge Mapping in the Field of Information Retrieval (IR): A Bibliometrics Analysis - Rahman, Ziaur; Sofik, Sk (Qualitative and Quantitative Methods in Libraries, 2022)
Information retrieval (IR) is the procedure of obtaining information system resources relevant to an information need from a collection of those resources. Information Retrieval (IR) has experienced tremendous growth over the years and has become the dominant form of Information access. The prime purpose of this study is to explore global scientific publications regarding Information Retrieval (IR) and mapping the recent global trends and visualization in this innovative research domain, thus provide future research directions based upon dynamic observations. With a bibliometric analytical framework, the study explores the Web of Science core collection database covering published materials from 2006 to 2020. Additionally, the article also developed a graphical visualization and knowledge mapping of the bibliographic literature by using the visualization of similarities viewer software, i.e., ScientoPY, Biblioshiny, Histcite, and VOS-viewer to map journals, keywords, and institutions with bibliographic co-occurrence of terms, topic, and co-citation analysis. The study carefully evaluates the current scenario of IR that will lead the researcher to form innovative initiatives to facilitate effective and further research.